การเพาะเลี้ยงสาหร่ายไก (Cladophora และ Microspora) ในน้ำหมักกากถั่วเหลือง - นาถนภา สุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Cultivated of edible freshwater alga known as Kai; Cladophora sp. and Microspora sp., in cement raceway ponds by adding fermented soybean cake water; the remnant from soymilk process 0, 5, 10 and 15% of soybean cake water were added 2 replications per treatment. Growth, protein and carotenoid value were measured for 8 weeks. The result showed that Growth, protein and carotenoid value were statistically significant different (p<0.05). Growth of Kai alga is highest in 3th week which can produced 9.50, 13.00, 20.00 and 10.00 gm-2(fresh weight) respectively. Protein value were 10.44, 12.20, 13.17 and 8.38% and carotenoid value were 468.75, 625.00, 1015.60, and 390.63 µg% (dry weight), respectively. Water quality during the cultivation of Kai alga showed that the highest of air temperature 36.71oC and pH 7.09 were statistically significant different among treatments (p<0.05), However, highest of water temperature 30.14oC and steam velocity 0.19 m/s were not statistically significant different among treatments (p>0.05) This research showed that cultivation of Kai alga by using fermented soybean cake water were best in 10% concentration for 3 weeks which can increase highest growth, protein and carotenoid value.